Effects of an imagery programme on the performance of federated and non-federated Boccia athletes - Amorim, André (2022)
The aim of this study was to analyse the effects and the relations through the implementation of an imagery (IM) training programme for federated and non-federated Boccia participants. Twenty-one Boccia athletes participated in this study. At the beginning of the study, and after a period of an 8-week IM training, the athletes’ IM ability (MIQ – 3) and their performance in Boccia tasks (distance to target and distance to coloured ball) were assessed. Data analysis was carried out using non-clinical magnitude-based inferences. The results suggests that, from pre to post test, federated and non federated athletes had a higher IM score and exhibited an improved performance. The performance levels seem to have been influenced by the participants’ level of expertise, with the non-federated athletes revealing higher magnitude of improvement than federated athlete’s. A non-significant correlation was observed between IM and performance. Although the inconsistency of the relationship between IM and performance, the results suggests that IM training enhances the development of IM ability and also motor actions in Boccia athletes.